DESIGNING SUPPLEMENTARY GRAMMAR MATERIALS BASED ON TASK BASED LANGUAGE TEACHING APPROACH - Fitri, Rapidah; Salam, Urai; Rezeki, Yanti Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to design supplementary grammar materials based on task-based language teaching (TBLT) approach as the teaching materials in teaching grammar to support the teaching-learning process in the classroom. Task-based language teaching approach focuses to make students as the center of the learning process and encourages the students’ motivation in learning grammar. Therefore, the grammar materials were designed and developed based on students’ contexts and the syllabus-used in the form of individual, pair, and group work. Each task is provided with task instruction. There are some features in each lesson that can help the teacher and students to understand the materials and tasks in each lesson. Those features are learning goals, lesson focuses and language focuses. The methods-used in this research were analyzing, designing, and developing. The validation checklists revealed that the supplementary grammar materials were scored between adequate and excellent. In addition, the supplementary grammar materials which were designed based on the result of interview data, book evaluation, curriculum 2013 and syllabus review indicate that the supplementary grammar materials are workable as the teaching materials in senior high school of Hidayatul Muslimin Islamic Boarding School 1 Pontianak. Keywords: Supplementary materials, Grammar materials, Grammar tasks, TBLT Approach, ADDIE Instructional Design.